Cisplatin-induced Ototoxicity in Children With Solid Tumor. Issue 2 (March 2019) - Wei, Meng; Yuan, Xiaojun
Abstract : Cisplatin is the principal chemotherapeutic agent and also tremendously increases the survival for pediatric patients with neuroblastoma or hepatoblastoma. With the extended overall survival period, clinical medical workers and parents gradually attach more attention to the late effect of chemotherapy of these children. The purpose of this study is to analyze the incidence and risk factors of cisplatin-based hearing loss. We retrospectively collected the archives of cisplatin-based chemotherapy and audiometric evaluation from 2005 through 2017 at Xinhua Hospital. From 384 patients treated with cisplatin, full data of 59 patients were available, and 14 cases (23.7%) were identified as significant hearing loss. The median time from usage of platinum compounds to the most recent audio test was 406 days. Cumulative and single maximum cisplatin dose was 622.6±283.2 and 137.6±51.6 mg/m 2 /cycle, respectively. Accumulated cisplatin dose (95% confidence interval, 1.001-1.006; P =0.012) and single maximum cisplatin dose (95% confidence interval, 1.000-1.029; P =0.049) were independently important predictors for moderate to severe hearing loss in children treated with cisplatin. Cisplatin can cause ototoxicity which profoundly handicap language development and social communication for children. Regular audiological management and long-term follow-up are strongly recommended for this vulnerable group.